3D printing of cordierite honeycomb structures and evaluation of compressive strength under quasi‐static condition. Issue 1 (15th October 2019) - Mamatha, Sirisala; Biswas, Papiya; Das, Dibakar; Johnson, Roy
Abstract: Ceramic honeycombs exhibit unique mechanical properties based on engineered formulations and geometry of cells. Extrusion of formable paste through a complex honeycomb die is the commonly practiced technique for the manufacturing of honeycombs globally. Extrusion die fabrication is a complex process which necessitates sophisticated infrastructure facilities that provide high geometrical accuracy and finish to produce defect free honeycombs. Furthermore, every configuration of honeycomb requires a specific tool. Additive manufacturing (AM)/ 3D printing is a rapid prototyping technique which offers flexibility in fabrication of honeycombs with desired geometries from a virtual model directly. Further, this does not require complicated dies. In this study, viscoplastic printable cordierite raw mix paste with a shear rate exponent of 0.87 was printed into honeycombs with hexagonal, square, and triangular cells using a ram type 3D printer. The printed honeycomb samples are found to possess good integrity and near net shape after drying. Sintered 3D‐printed honeycomb samples of all configurations have exhibited cordierite as a major phase along with minor phases of magnesium aluminate (MgAl2 O4 ) spinel, clinoenstatite (MgSiO3 ), and corundum (Al2 O3 ) with sintered density of 2.41‐2.48 g/cc. The samples are also subjected to compression testing under quasi‐static condition. The study demonstrates 3D printing as a viable and flexible technique for rapid prototyping of honeycombs with desired configurations and engineered properties.